Peran Kepala Sekolah dalam Optimalisasi Branding Sekolah melalui Literasi Budaya dan Literasi Digital di SMA Negeri 1 Gresik - Lilik Suharnani; Mohammad Syahidul Haq; Muhamad Sholeh; Ayu Wulandari; Amrozi Khamidi; Mochamad Nursalim (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study was to identify and analyze the role of the principal in efforts to improve school branding through cultural and digital literacy at SMA Negeri 1 Gresik. Strong school branding not only builds a positive image of the school but also attracts prospective students and strengthens the relationship between the school and the surrounding community. This study uses a qualitative approach with a case study method at SMA Negeri 1 Gresik. In this study, data were collected through in-depth interviews with the principal, vice principal, teachers, and staff, literacy activists, students and through observation and documentation related to cultural and digital literacy activities carried out. The results of the study showed that the principal acted as a strategic leader who initiated local culture-based activities, such as the use of Gresik batik and the introduction of traditional culinary, as well as a facilitator in the integration of digital technology, such as the use of social media for publication of school activities. In conclusion, the impact of implementing this cultural and digital literacy strategy can be seen in the increasing public trust and student participation in cultural activities, especially the culture of the city of Gresik. Keywords: Principal, School Branding, Cultural and Digital Literacy